2017
DOI: 10.1111/ijfs.13636
|View full text |Cite
|
Sign up to set email alerts
|

Application of an antimicrobial packaging material from chicken bone gelatine and cinnamon bark oil to mozzarella cheese

Abstract: Summary Chicken bones are mostly discarded even though they contain a considerable amount of proteins, which would allow them to be applicable as a protein film source. In this study, chicken bone gelatine (CBG) films were prepared and characterised after the addition of cinnamon bark oil (CBO) to confer antimicrobial activity. The incorporation of 1% CBO increased the tensile strength of the CBG film from 18.2 to 23.9 MPa, whereas elongation at break was decreased from 15.6% to 5.91% and water solubility from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…The antimicrobial activities of the films containing OT with different concentrations against the four common pathogens were determined using the disc diffusion assay described by Kim et al [ 45 ]. L. monocytogenes (KCTC 13064, ATCC 15313), S. aureus (KCTC 1621, ATCC 10537), E. coli O157:H7 (ATCC 43889, NCTC 12079), and S. typhimurium (ATCC 14028, KCTC 2421) inocula at concentrations of 6–7 log CFU/mL were spread onto the surface of Mueller Hinton Agar media.…”
Section: Methodsmentioning
confidence: 99%
“…The antimicrobial activities of the films containing OT with different concentrations against the four common pathogens were determined using the disc diffusion assay described by Kim et al [ 45 ]. L. monocytogenes (KCTC 13064, ATCC 15313), S. aureus (KCTC 1621, ATCC 10537), E. coli O157:H7 (ATCC 43889, NCTC 12079), and S. typhimurium (ATCC 14028, KCTC 2421) inocula at concentrations of 6–7 log CFU/mL were spread onto the surface of Mueller Hinton Agar media.…”
Section: Methodsmentioning
confidence: 99%
“…Kim et al. () reported that mozzarella cheese wrapped with a chicken bone gelatin film containing 1% cinnamon bark essential oil demonstrated antimicrobial activity against Listeria monocytogenes for 20 days. Our results suggest that the SSP/PLA‐laminated films containing CBO can be applied under real food storage conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The absorbance was measured at 734 nm. FRAP was evaluated (Kim et al., ). The film solution (200 μL) and FRAP solution (3800 μL) were mixed and reacted.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations